Deregulation in a Time of Pandemic: Does Pollution Increase Coronavirus Cases or Deaths? - Claudia Persico; Kathryn R. Johnson (Institute of Labor Economics (IZA), 2020)
The COVID-19 virus, also known as the coronavirus, is currently spreading around the world. While a growing literature suggests that exposure to pollution can cause respiratory illness and increase deaths among the elderly, little is known about whether increases in pollution could cause additional or more severe infections from COVID-19, which typically manifests as a respiratory infection. Using variation in pollution induced by a rollback of enforcement of environmental regulations by the Environmental Protection Agency (EPA) and a difference in differences design, we estimate the effects of increased pollution on county-level COVID-19 deaths and cases. Despite popular media coverage to the contrary, we find that counties with more Toxic Release Inventory (TRI) sites saw increases in pollution following the EPA's rollback of enforcement, while counties with fewer sites saw a smaller increase in pollution. We find that increases in pollution are associated with increases in cases and deaths from COVID-19.
Keywords: Q53; I10; I14; 330; pollution; COVID-19; coronavirus; health; mortality